Citrullus colocynthis (L.) Schrad (Bitter Apple Fruit): Promising Traditional Uses, Pharmacological Effects, Aspects, and Potential Applications - Li, Qin-Yuan; Munawar, Mahzaib; Saeed, Muhammad; Shen, Ji-Qiang; Khan, Muhammad Sajjad; Noreen, Sobia; Alagawany, Mahmoud; Naveed, Muhammad; Madni, Asadullah; Li, Chang-Xing (Frontiers in Pharmacology, 2022)
Health consciousness and an increase in knowledge about the side effects of synthetic drugs tend to further enhance the interest in traditional medicines. Medicinal plants help to cure diseased conditions for further improved living, so the importance of the ethnomedicinal study was realized by the population and more use of herb-based medicines has come in demand for further use. Citrullus colocynthis is an herbaceous plant packed with an abundance of nutrients that play a key role in the improvement of wellbeing. C. colocynthis was found to have many biological effects such as antioxidant, hypoglycemic, antibacterial, anticancer, anti-inflammatory, analgesic, gastrointestinal tract, reproduction, protection, anti-microbial, antidiabetic, hypolipidemic, antineoplastic, profibrinolytic, analgesic, anti-allergic, pesticidal and immune-stimulant activity. There are numerous bioactive compounds like cucurbitacin, flavonoids, and polyphenols present in C. colocynthis which are further responsible for medicinal properties. Fewer data about its use and inclusion level on human and poultry studies need to be debated. Owing to the confined data about the use of C. colocynthis in animals especially poultry, it is the first reassessment to propose C. colocynthis plant and its extract for use in the poultry industry and to expose the vital importance of C. colocynthis for human health. Hence, the goal of this study was to draw out information on the useful health component of C. colocynthis as well as to appeal to the interest of researchers of medical fields, veterinarians, and poultry nutritionists in the direction of the significance of C. colocynthis in humans, veterinary and poultry.